PENGARUH PROFITABILITAS DAN STRUKTUR AKTIVA TERHADAP KEPUTUSAN PENDANAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2006-2008 - Saragih, Joana L (UNIKA Santo Thomas, 2011)
The purpose of research is to analyze the factors that total debt and equity of manufacturing company. There are two factors will be analyzed, they are profitability and assets structure. This research used 12 samples of manufacturing companies which listed in Indonesia Stock Exchange in 2006-2008. The secondary data that were contained in Indonesian Capital Market Directory were used as data sourse.The hypothesis was tested using multiple linear regression method and the data were processed using SPSS program. Result of this research shows that profitability and assets structure simultaneously significant influence to funding decision of total debt and equity of manufacturing companies. While partially, profitability negative significant influence to funding decision of total debt and equity, and assets structure positive significant influence to funding decision of total debt and equity. While simultan, profitability and assets structure significant influence to funding decision of total debt and equity. Assets structure influential dominance to funding decision of total debt and equity.